2018
DOI: 10.1145/3185378
|View full text |Cite
|
Sign up to set email alerts
|

Threesomes, Degenerates, and Love Triangles

Abstract: The 3SUM problem is to decide, given a set of n real numbers, whether any three sum to zero. It is widely conjectured that a trivial Opn 2 q-time algorithm is optimal and over the years the consequences of this conjecture have been revealed. This 3SUM conjecture implies Ωpn 2 q lower bounds on numerous problems in computational geometry and a variant of the conjecture implies strong lower bounds on triangle enumeration, dynamic graph algorithms, and string matching data structures.In this paper we refute the 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
60
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 65 publications
1
60
0
Order By: Relevance
“…Indeed, for a long time it was conjectured that no subquadratic decision tree exists for 3SUM [57] and an (n 2 ) lower bound is known in a restricted linear decision tree model [4,40]. However, in a recentand in our opinion quite astonishing-result, Grønlund and Pettie showed that if we allow only slightly more powerful algebraic decision trees than in the previous lower bounds, one can decide 3SUM non-uniformly in O(n 2−ε ) steps, for some fixed ε > 0 [52]. They also show that this leads to a general subquadratic algorithm for 3SUM, a situation very similar to the Fréchet distance as described in the present paper.…”
Section: Recent Developmentsmentioning
confidence: 93%
“…Indeed, for a long time it was conjectured that no subquadratic decision tree exists for 3SUM [57] and an (n 2 ) lower bound is known in a restricted linear decision tree model [4,40]. However, in a recentand in our opinion quite astonishing-result, Grønlund and Pettie showed that if we allow only slightly more powerful algebraic decision trees than in the previous lower bounds, one can decide 3SUM non-uniformly in O(n 2−ε ) steps, for some fixed ε > 0 [52]. They also show that this leads to a general subquadratic algorithm for 3SUM, a situation very similar to the Fréchet distance as described in the present paper.…”
Section: Recent Developmentsmentioning
confidence: 93%
“…There are now known to be O(n 2 / poly(log n)) algorithms for both integer inputs [5] and real inputs [47]. The Integer 3SUM Conjecture asserts that the problem requires Ω(n 2−o(1) ) time, even if A ⊂ {−n 3 , .…”
Section: Introductionmentioning
confidence: 99%
“…Of course, the plausibility of the 3SUM and OMv conjectures continue to be actively scrutinized. Stronger forms of the 3SUM and OMv conjectures have already been refuted; see [47,59].…”
Section: Introductionmentioning
confidence: 99%
“…The conjecture that it cannot be solved in O(n 2−ε ) time (in the real or integer setting) has been used as a basis for proving conditional lower bounds for numerous problems from a variety of areas (computational geometry, data structures, string algorithms, and so on). See previous papers (such as [22]) for more background.…”
mentioning
confidence: 99%
“…In a surprising breakthrough, Grønlund and Pettie [22] discovered the first subquadratic algorithms for 3SUM. They showed the decision-tree complexity of the problem is O(n 3/2 √ log n), and gave a randomized O((n 2 / log n)(log log n) 2 )-time algorithm and a deterministic O((n 2 / log 2/3 n)(log log n) 2/3 )-time algorithm in the standard real-RAM model.…”
mentioning
confidence: 99%